THE ROLE OF THE STATE IN DEVELOPMENT OF INTEGRATED BUSINESS STRUCTURES - R. N. Fedosova (Стратегические решения и риск-менеджмент)
The article deals with the essence of integrated business groups (IBG), provides the assessment of their current state and dynamics, outlines the factors determining IBG development. The results generalize the world experience in the state’s participation in IBG development. The paper also presents modern forms of interaction and interpenetration of the state and IBG.